Case Study of HELLP Syndrome in a pregnant woman of African Descent in Jos, North Central Nigeria - Williams, B. , Goshit, S.J. , Kuschak, D. , Erhabor, O.* , Erhabor, T. , Egenti, N.B. (Sokoto Journal of Medical Laboratory Science)
HELLP (haemolysis, elevated liver enzymes, low platelets) is a pregnancy- associated hypertensive syndrome that constitutes one of the clinical forms in the range of pre-eclampsia. It is a severe complication seen in pregnant women usually in the second trimester of pregnancy. We describe a 31-year-old primigravidae with twins who presented at 16/40 with history of epigastric pain raised BP 240/140mmHg with signs of HELLP [signs of haemolysis (raised bilirubin (direct and indirect of 17.8 and 4.8 µmol/L respectively), elevated liver enzymes (AST and ALT of 47 and 48 iu/L) and low platelet count (81x10 9 /L)]. The patient situation worsened significantly and a decision was taken by the managing team after obtaining consent from the patient and her partner to terminate the pregnancy to save the mother's life. With effective management and excellent supportive care, all laboratory derangements, including liver enzymes normalised after 2 weeks.